1998
DOI: 10.1161/01.atv.18.5.833
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Consumption of Green and Black Tea on Plasma Lipid and Antioxidant Levels and on LDL Oxidation in Smokers

Abstract: Abstract-Intake of flavonoids is associated with a reduced cardiovascular risk. Oxidation of LDL is a major step in atherogenesis, and antioxidants may protect LDL from oxidation. Because tea is an important source of flavonoids, which are strong antioxidants, we have assessed in a randomized, placebo-controlled study the effect of consumption of black and green tea and of intake of isolated green tea polyphenols on LDL oxidation ex vivo and on plasma levels of antioxidants and lipids. Healthy male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 66 publications
7
115
1
4
Order By: Relevance
“…2.5). These levels were comparable in the four groups and did not change during the intervention period (Princen et al, 1998).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…2.5). These levels were comparable in the four groups and did not change during the intervention period (Princen et al, 1998).…”
Section: Resultsmentioning
confidence: 77%
“…None of the participants reported any side effects. Dietary intake of antioxidants vitamin C, vitamin E, bcarotene, and¯avonoids (quercetin, myricetin and kaempferol, corrected for¯avonoids from tea) was similar before and at the end of the study (Princen et al, 1998).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The increase in serum levels of vitamins A and E can be attributed to the ability of verbascoside to strengthen and save the endogenous antioxidant system, controlling oxidative metabolism by reducing the production of reactive radical species and increasing the antioxidant activity of enzymes (Princen et al, 1998;Zhu et al, 1999;Liao and Yin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is because quercetin is not signi®cantly incorporated into the LDL particle. This would explain the ®nding of a number of recent in vivo studies which have concluded that the ingestion of tea, a beverage rich in¯avonoids, does not protect the LDL against oxidation in vivo (van het Hof et al, 1997;McAnlis et al, 1998;Princen et al, 1998). The¯avonoids may be absorbed from the tea into the plasma, as shown by Lee et al (1995), but become bound to the plasma proteins leaving them unable to protect the LDL particle against oxidation.…”
Section: Discussionmentioning
confidence: 99%